Efeito da lâmina de água e da frequência de irrigação por gotejamento na cultura de pimentão: II — Produção de sementes - Caixeta, Tarciso José; Dias Casali, Vicente Wagner; Bernardo, Salassier; Maffia de Oliveira, Laede (Revista Ceres, 2025)
The effects water depth (2-4-6 mm/day) and irrigation frequency (1-2-3 days) Were studied on the seed production and seed germination characteristics of sweet pepper (Capsicum annuum L.) cv. ‘Cascadura Ikeda’) at Ponte Nova in the State of Minas Gerais. The trickle irrigation system was used as the water source. The highest water depth (6 mm) promoted higher seed yield in normal fruits, while injured fruits had their maximum production at a water depth of 4.6 mm/day. The irrigation frequency did not greatly affect the seed yield of the fruits. The germina- tion energy and the percentage of seed germination of the fruits were not affected either by water depth or irrigation frequency. The observed values for the germi- nation capacity of the seeds and the germination velocity of the seeds were greatly superior to the minimum standard germination values for sweet peppers.